Artificial Intelligence (AI)-Powered Line Follower Robot with Hurdle Detection and Voice Control (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: In this paper, we propose a voice controlled line following robot with the ability to trace the set path and avoid hurdles while moving autonomously. Line-following robots have been around for decades, but this setup uses AI algorithms and fresnel lenses to improve accuracy More Traditional line-following robots often face drawbacks in dealing with intricate environments, but those are addressed here via user control over voice recognition, as-well-as obstacle detection through ultrasonic sensors. The robot is controlled over an Arduino UNO microcontroller and the (advance) features that it offers allows the robot to operate independently with lesser human interactions, the applications of such a robot will span across Transportation & logistics, Industrial Automation and Personal Assistance. This study reveals the potential of this robot to improve precision and flexibility in a realistic usage condition, thereby providing an important tool for automation with safety and productivity.